INTEGRATING AI INTO ESP COURSE TO IMPROVE LANGUAGE LEARNING THROUGH SMART AND EFFECTIVE STRATEGIES (Scientific journal of the Fergana State University, 2025)
This study explores the integration of Artificial Intelligence (AI) into English for Specific Purposes (ESP) courses to enhance language learning through smart and effective strategies. The research focuses on the perspectives of students and educators at Fergana State University in Uzbekistan, examining their familiarity with AI tools, preferences, and perceived advantages and challenges. The findings reveal that AI chatbots are the most favored tool for ESP learning, with 59.38% of respondents valuing their interactive and real-time feedback capabilities. Personalized learning is identified as the greatest advantage of AI, with 56.25% of respondents highlighting its ability to tailor lessons to individual needs. However, challenges such as over-reliance on AI and ethical concerns are also noted. The study concludes that while AI has significant potential to revolutionize ESP education, it should be used as a complementary tool alongside traditional teaching methods. The research offers practical insights for educators and policymakers in Uzbekistan, emphasizing the need for a balanced approach to AI integration in language learning.